ROLE OF ARTIFICIAL INTELLIGENCE IN EFFECTIVE OPERATIONS OF FINANCIAL TECHNOLOGY: AN EMPIRICAL STUDY (Journal of Pharmaceutical Negative Results, 2023)
The capabilities of Artificial Intelligence is transforming its operations by providing them with more effective risk and fraud management processes for better product offerings. We will also discuss through this context how they are reshaping the client’s experiences and being increasingly deployed. Results of this research will definitely enable everyone to receive more information to meet the requirements of their customers and consumers in this global financial system in all financial spheres. This technology is a combination of numerous technologies and is considered in order to monitor substantive issues and capture market improvements. Applications of Artificial Intelligence are changing day by day across the world to ensure low income earners, the poor, women and youths so that they can participate in mainstream financial market. There are few speculations and many opinions about the Artificial Intelligence that they may have negative effect on the financial sector. This paper encompasses numerous researches in this field of AI in order to explain its relevance as well as effectiveness thoroughly in upcoming future. A sample of 193 respondents was collected from respondents through a "standard questionnaire," which was created on a five-point interval scale.